Pemikiran Pendidikan Islam Harun Nasution: Menghadirkan Pascasarjana pada Perguruan Tinggi Agama Islam - Fauziah, Nurul; Ondeng, Syarifuddin; Yahdi, Muh. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Harun Nasution is an Islamic thinker who has made significant contributions to the reform of Islamic education in Indonesia. One of his monumental ideas is the establishment of postgraduate programs at State Islamic Universities (PTIN), such as at IAIN which is now UIN. Higher education in Indonesia, especially in the context of Islamic education, has experienced rapid development, but still faces challenges in integrating science with religious values. Harun Nasution, as one of the great thinkers in Islamic education, offers a very relevant perspective in answering this challenge. Harun Nasution's Islamic educational thinking emphasizes the importance of education that combines religious knowledge with modern science. This article aims to analyze Harun Nasution's thoughts on Islamic education and their relevance to the development of postgraduate programs at state universities in Indonesia. Through a qualitative approach, this article shows that Harun Nasution's thoughts can be a basis for curriculum renewal, increasing the capacity of lecturers, and developing research based on the integration of religious knowledge and science. Thus, postgraduate education at state universities in Indonesia is expected to produce graduates who are academically competent and have real contributions to the progress of the people and the nation.